The effect of perceived usefulness, trust and perceived risk on online purchase intention - Dinda Suchi Wulandari; Rosyeni Rasyid (Operations Management and Information System Studies, 2022)
This research aims to analyze the effect of perceived usefulness, trust and perceived risk on purchase intentions on the Sociolla online shopping in Padang City. 250 respondents were the sample of this study. Data is processing by SmartPLS software and collected from online questionnaire. The results of this study showed that (1) perceived usefulness has a significant positive effect on perceived risk. (2) trust has no significant effect on perceived risk. (3) perceived usefulness has a significant positive effect on purchase intention. (4) trust has a significant positive effect on purchase intention. (5) perceived risk has no significant effect on purchase intention. (6) perceived usefulness has no effect on purchase intention through perceived risk. (7) trust has no effect on purchase intention through perceived risk.